St John’s Wort (Hypericum perforatum) versus Sertraline and Placebo in Major Depressive Disorder: Continuation Data from a 26-Week RCT - Sarris, J.; Fava, M.; Schweitzer, I.; Mischoulon, D. (Pharmacopsychiatry, 2012)
Hypericum perforatum (St John’s wort: SJW) has been extensively studied as an antidepressant in short-term trials, however little research has been conducted on longer-term efficacy.Our objective was to analyze the continuation data from a 26-week randomized, double-blind, controlled study of SJW (LI-160) vs. sertraline and placebo in major depressive disorder. 124 participant “responders” continued treatment after week 8, until week 26. They continued randomly assigned SJW (900–1 500 mg), sertraline (50–100 mg) or matching placebo.At week 26, on the primary outcome, Hamilton depression rating scale (HAM-D) completer scores were: SJW (6.6±4.5), sertraline (7.1±5.4) and placebo (5.7±5.4) with a significant effect for time (p=0.036). Comparisons between all treatments were however non-significant (p=0.61). This effect was mirrored on the other outcomes: the BDI, CGI-severity, CGI-improvement, and on intention-to-treat analyses.While the continuation data revealed an equivocal outcome between treatments at week 26, both SJW and sertraline were still therapeutically effective, with a pronounced “placebo-effect” impeding a significant result at week 26.
Keywords: St John’s wort; Hypericum perforatum; sertraline; antidepressants; randomized controlled trial; depression; herbal medicine